Regional Work Unit Budgeting Process at the Archives and Library Service of West Sumatra Province - Fadhlan, Fadhlan (STIA Adabiah, 2023)
This research aims to describe the budgeting process and obstacles, as well as the efforts made to overcome obstacles that arise in the budgeting process at the West Sumatra Province Archives and Library Service. This research will use a qualitative descriptive method, or the author will provide and describe symptoms, facts, and events clearly regarding the Regional Work Unit Budgeting Process at the Archives and Library Service of West Sumatra Province. Researchers used informant selection techniques using the purposive sampling method. This type of research, namely qualitative research with descriptive methods, is carried out for data validity through triangulation techniques. Based on the research results, it was found that the budgeting process has many twists and turns, including rules and implementation processes that must be followed. From planning to evaluation and monitoring, everything goes according to predetermined stages. However, in this stage of the process, human resources are needed to support its implementation. Apart from that, the attitude of commitment and responsibility as a state apparatus must be maintained and can be improved to create good quality work, be able to compete well, and work hard in carrying out their duties and responsibilities to achieve excellent service and improve the welfare of the community.